2007
DOI: 10.1152/ajplung.00412.2006
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and annexin II cell surface translocation mediate airway epithelial wound repair

Abstract: Glycosylation of cell surface proteins can regulate multiple cellular functions. We hypothesized that glycosylation and expression of glycoproteins after epithelial injury is important in mediating repair. We report the use of an in vitro culture model of human airway epithelial cells (1HAEo(-)) to identify mediators of epithelial repair. We characterized carbohydrate moieties associated with repair by their interaction with the lectin from Cicer arietinum, chickpea agglutinin (CPA). Using CPA, we identified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Both AnxA2 and S100A10/p11 are expressed in the stratified epithelium (56)(57)(58), but AnxA2 expression in intact and wounded skin is more concentrated to the surface of basal cells (57,58). Currently, there is no direct evidence to suggest that a cellular receptor dictates cell-or tissue-specific tropism for papillomaviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both AnxA2 and S100A10/p11 are expressed in the stratified epithelium (56)(57)(58), but AnxA2 expression in intact and wounded skin is more concentrated to the surface of basal cells (57,58). Currently, there is no direct evidence to suggest that a cellular receptor dictates cell-or tissue-specific tropism for papillomaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…AnxA2 is predominantly expressed in the endocervix and basal layers of epithelia and the ectocervix (56,58), whereas S100A10 is expressed in both basal and suprabasal cells (57). Upon HK wounding in culture, AnxA2 expression increases at the cell surface (58), and knockdown of AnxA2 alters wound-induced HK migration (59).…”
mentioning
confidence: 99%
“…Annexin A2 was implicated in wound closure in several studies. Patchell et al [204] examined the role of glycosylation and expression of glycoproteins after epithelial injury and demonstrated that following injury, N-glycosylation events and annexin A2 presentation on the cell surface of airway epithelial cells are important mediators in repair [204]. Following mechanical wounding of confluent monolayers of human airway epithelial cells, glycosylation staining increased on the cell surface of groups of cells in the proximity of the wound edge.…”
Section: Cellular Stress and Membrane Repairmentioning
confidence: 99%
“…Paraffin-embedded sections of normal lung parenchyma from patients undergoing lung resection were obtained from the Tissue Registry (iCAPTURE Centre, Vancouver). Slides were processed with standard techniques of Citra buffer heat-induced antigen retrieval procedure (Dako, Mississauga), Following blocking, slides were incubated in primary antibody (rabbit anti-EPOR 1:50 or rabbit IgG isotype control 1:200) overnight at 4uC and immunostained as previously described [23].…”
Section: Immunohistochemistrymentioning
confidence: 99%